Profiling of microRNAs in tumor interstitial fluid of breast tumors – a novel resource to identify biomarkers for prognostic classification and detection of cancer. Issue 2 (12th December 2016) - Halvorsen, Ann Rita; Helland, Åslaug; Gromov, Pavel; Wielenga, Vera Timmermans; Talman, Maj‐Lis Møller; Brunner, Nils; Sandhu, Vandana; Børresen‐Dale, Anne‐Lise; Gromova, Irina; Haakensen, Vilde D.
Abstract : It has been hypothesized based on accumulated data that a class of small noncoding RNAs, termed microRNAs, are key factors in intercellular communication. Here, microRNAs present in interstitial breast tumor fluids have been analyzed to identify relevant markers for a diagnosis of breast cancer and to elucidate the cross‐talk that exists among cells in a tumor microenvironment. Matched tumor interstitial fluid samples (TIF, n = 60), normal interstitial fluid samples (NIF, n = 51), corresponding tumor tissue specimens ( n = 54), and serum samples ( n = 27) were collected from patients with breast cancer, and detectable microRNAs were analyzed and compared. In addition, serum data from 32 patients with breast cancer and 22 healthy controls were obtained for a validation study. To identify potential serum biomarkers of breast cancer, first the microRNA profiles of TIF and NIF samples were compared. A total of 266 microRNAs were present at higher level in the TIF samples as compared to normal counterparts. Sixty‐one of these microRNAs were present in > 75% of the serum samples and were subsequently tested in a validation set. Seven of the 61 microRNAs were associated with poor survival, while 23 were associated with the presence of immune cells and adipocytes. To our knowledge, these data demonstrate for the first time that profiling of microRNAs in TIF can identify novel biomarkers for the prognostic classification and detection of breast cancer. In addition, the present findings demonstrate that microRNAs may represent the cross‐talk that occurs between tumor cells and their surrounding stroma. Abstract : Tumor cells, tumor interstitial fluid (TIF), normal interstitial fluid, and serum all have a distinct microRNA profile. Specific microRNAs detected in TIF are associated with the presence of tumor‐infiltrating lymphocytes and adipocytes, reflecting the cross‐talk between the cells in stroma. Only a portion of these microRNAs are detected in serum, but are attractive candidates for biomarkers of breast cancer.